2013
DOI: 10.1179/1743284713y.0000000259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B and Ti on hot ductility of high Al and high Al, Nb containing TWIP steels

Abstract: The addition of ∼0·002B and ∼0·04Ti as microalloying additions to improve the poor hot ductility and high risk of cracking on continuous casting of high Al containing twinning induced plasticity (TWIP) steels has been examined. Tensile specimens were either cast in situ or heated to 1250°C before cooling at 60 K min−1 to test temperatures in the range 700–1100°C and strained to failure at 3×10−3 s−1. For tensile specimens reheated to 1250°C, the presence of B with sufficient Ti to combine with all the N improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The work has shown that a low S and P content (preferably ~0.005%), by reducing the volume fraction of sulphides [5,7] and in the case of P preventing the low melting point iron phosphide phase forming, gives rise to better ductility [7]. More importantly, it is found that a small addition of B is needed so it can segregate to the boundaries and strengthen them [6]. In order for this to occur, the B must remain in solution and be protected by adding Ti to combine with all the N so that BN is prevented from forming.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The work has shown that a low S and P content (preferably ~0.005%), by reducing the volume fraction of sulphides [5,7] and in the case of P preventing the low melting point iron phosphide phase forming, gives rise to better ductility [7]. More importantly, it is found that a small addition of B is needed so it can segregate to the boundaries and strengthen them [6]. In order for this to occur, the B must remain in solution and be protected by adding Ti to combine with all the N so that BN is prevented from forming.…”
mentioning
confidence: 99%
“…The cooling rate in previous work [3,5,8] after reheating has generally been 60 o C/min, which is higher than the recommended cooling rate of ≤25 o C/min needed to coarsen the TiN particles to obtain the maximum ductility or to give the maximum segregation for B to strengthen the grain boundaries [13]. In this exercise two cooling rates, 12 o C/min min and 60 o C/min have been examined.…”
mentioning
confidence: 99%
See 3 more Smart Citations